Assessment of the mannose inhibition on tobacco regeneration for establishment of a mannose selection system for transgenic plants - Thủy, Lê Thị; Hằng, Triệu Thị; Nhân, Lâm Đại; Sơn, Lê Văn (Vietnam Journal of Biotechnology, 2016)
Recently, the application of environmentally friendly methods in transgenic-plant selection has been exploited with an interest to contribute to the commercialization of transgenic products. In this study, mannose was chosen in selecting transgenic tobacco. The ability of mannose to inhibit tobacco regeneration was assessed through three stages: creating multi-shoot, elongating shoot, and rooting of tobacco cultivars K326 and C9-1. The results showed that mannose concentrations at 30 g/l and 20 g/l are suitable for creating multi-shoot of K326 and C9-1, respectively. In addition, mannose concentration at 30 g/l in combination with 7,5 g/l sucrose is fit for elongating shoot while its concentration at 30 g/l is appropriate for rooting transgenic tobacco in both K326 and C9-1 cultivars. The mannose selection of transgenic tobacco using gus gene showed that the transgenic effectiveness is ranging 16-17% of K326 and 9-11% of C9-1 cultivars. The successful establishment of mannose selection system in transgene tobacco contributes to generate bio-safety transgenic plants